Integrasi sustainability dan MCDM untuk kelayakan teknologi sterilisasi pada pendirian pabrik CPO terintegrasi palm kernel oil - Sawarni Hasibuan; Hermawan Thaheer (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
In the palm oil processing, one of the most important stages is boiling the fresh fruit bunches or sterilization, because it greatly determines the yield and quality of the CPO produced. The purpose of this study was to analyze the selection of sterilizer technology by considering the sustainability factor. A case study was conducted at PTPN V which is planning to expand its production capacity. The data used in this study consisted of primary data and secondary data. Primary data obtained from distributing questionnaires, interviews and field observations. Respondents of this study were stakeholders of the palm oil mill and PTPN V. This research combines qualitative and quantitative approaches. Qualitative analysis was conducted to describe the sterilization technology for processing fresh oil palm fruit bunches into CPO. Financial viability is evaluated based on the best sterilization technology recommendations. The results of the analysis recommend horizontal sterilized-indexer technology as a priority, followed by vertical sterilization technology and continuous sterilization technology. By paying attention to the sustainability criteria, the PKS design is integrated with PKO. This integration has implications for energy efficiency, kernel transportation, other utility facilities, and even a number of work units and personnel. The investment for the construction of PKS with a capacity of 45 tons/hour using horizontal-indexer sterilization technology requires a fund of IDR 170.8 billion were declared feasible with an IRR of 26.64%, a positive NPV, a B/C ratio of 2.23, and a PBP of 6 years and 5 months. The results of the sensitivity analysis to the assumption of an increase in production costs of 6 percent have not changed the recommendation, as well as a decrease in factory processing capacity by 6 percent.